Effects of late “visits” re-booking practice at Mpilo and Parirenyatwa hospitals Opportunistic Infections clinics for the HIV/AIDS & TB Programme in the Ministry of Health and Child Care - Chawurura, Trymore (Midlands State University, 2017)
Worldwide, an estimated 34 million people were living with HIV, but only 47% of the people in low- and middle-income countries eligible for antiretroviral therapy (ART) were receiving treatment at the end of 2013. Zimbabwe initiated its national ART programme in April 2004, and since that time the benefits of such therapy have been widely documented in the country. The scaling up of the ART programme is facilitated by the identification and approval of ART-initiating sites using standardized assessment tools and simplified treatment guidelines that employ the public-health approach as well as the family-centred approach. It is now widely accepted that even resource-poor countries using a public-health approach to HIV and AIDS care and treatment can achieve similar effectiveness with these antiretrovirals (ARVs)as observed inmore affluent settings.